Radiologic screening and surveillance in hereditary cancers. (2022) - Clarke, Jamie E.; Magoon, Stephanie; Forghani, Irman; Alessandrino, Francesco; D'Amato, Gina; Jonczak, Emily; Subhawong, Ty K.
Abstract: Hereditary cancer syndromes comprise an important subset of cancers caused by pathogenic germline mutations that can affect various organ systems. Radiologic screening and surveillance for solid tumors has emerged as a critical component of patient management in permitting early cancer detection. Although imaging surveillance may be tailored for organ-specific cancer risks, surveillance protocols frequently utilize whole-body MRI or PET/CT because of their ability to identify neoplasms in different anatomic regions in a single exam. In this review, we discuss the basic tenets of imaging screening and surveillance strategies in these syndromes, highlighting the more common neoplasms and their associated multimodality imaging findings. Highlights: Pathogenic germline mutations in hereditary cancers cause early-onset distinctive tumors in an organ-specific pattern. Geneticist, oncologist, and radiologist coordination facilitates syndrome-appropriate screening and surveillance strategies. WB-MRI is a promising comprehensive non-ionizing screening/surveillance modality but with sparse prospective survival data.